EDUKASI IBU BALITA MELALUI PEMBERDAYAAN KELAS IBU BALITA DI DESA PUKDALE KABUPATEN KUPANG - Yosefa Sarlince Atok; Roslin E. M. Sormin; Nabilah Nurul Ilma; Maria Vilastry Nuhan; Avelina Paskalia Gusman (Universitas Mataram, 2023)
Mother's knowledge and skills are very important during pregnancy, childbirth, postpartum, infant and toddler care. The mother class is a study group for pregnant women, breastfeeding mothers and mothers of toddlers. Classes for pregnant women are facilitated by midwives using the mother class package, namely the KIA book, guidelines for implementing classes for pregnant women, guidelines for administering classes for mothers under five, pregnant women and lactating mothers, handouts for class facilitators for mothers under five. This activity aims to increase knowledge and awareness in various ways, including; exclusive breastfeeding, immunization for infants, provision of MP-ASI and balanced nutrition for toddlers, monitoring growth and carrying out stimulation of toddler development, dental care for toddlers and proper hand washing, common diseases in toddlers. This activity was carried out in Pukdale Village, Kupang Regency. The targets and partners in this activity were mothers under five, cadres, village midwives, health center midwives, lecturers and students of the Midwifery Study Program STIKes Maranatha Kupang. The results of this activity indicate that the use of the MCH handbook during ANC by pregnant women can increase adequate knowledge about pregnancy, childbirth, exclusive breastfeeding, infant and toddler care, classes for mothers under five, management of classes for mothers under five by increasing the knowledge and abilities of mothers under five in health care babies under five before (60%) and after education (85%), there is also a handbook for Mothers under five before (55%) and after education (85%). The conclusions of the health education activities were successfully carried out with the results of increasing knowledge and skills, changing attitudes and behavior of mothers by using the MCH handbook in realizing optimal growth and development of toddlers.